Stimulatory Effect of Intermittent Hypoxia on the Production of Corticosterone by Zona Fasciculata-Reticularis Cells in Rats - Hwang, Guey-Shyang (Sci Rep, 2017)
Hypoxia or intermittent hypoxia (IH) have known to alter both synthesis and secretion of hormones. However, the effect of IH on the production of adrenal cortical steroid hormones is still unclear. The aim of present study was to explore the mechanism involved in the effect of IH on the production of corticosterone by rat ZFR cells. Male rats were exposed at 12% O(2) and 88% N(2) (8 hours per day) for 1, 2, or 4 days. The ZFR cells were incubated at 37 °C for 1 hour with or without ACTH, 8-Br-cAMP, calcium ion channel blockers, or steroidogenic precursors. The concentration of plasma corticosterone was increased time-dependently by administration of IH hypoxia. The basal levels of corticosterone production in cells were higher in the IH groups than in normoxic group. IH resulted in a time-dependent increase of corticosterone production in response to ACTH, 8-Br-cAMP, progesterone and deoxycorticosterone. The production of pregnenolone in response to 25-OH-C and that of progesterone in response to pregnenolone in ZFR cells were enhanced by 4-day IH. These results suggest that IH in rats increases the secretion of corticosterone via a mechanism at least in part associated with the activation of cAMP pathway and steroidogenic enzymes.